CMR-based right ventricular strain analysis in cardiac amyloidosis and its potential as a supportive diagnostic feature. (February 2023) - Eckstein, Jan; Körperich, Hermann; Weise Valdés, Elena; Sciacca, Vanessa; Paluszkiewicz, Lech; Burchert, Wolfgang; Farr, Martin; Sommer, Philipp; Sohns, Christian; Piran, Misagh
Abstract: Background: Right ventricular (RV) strain has provided valuable prognostic information for patients with cardiac amyloidosis (CA). However, the extent to which RV strain and strain rate can differentiate CA is not yet clinically established. CA underdiagnosis delays treatment strategies and exacerbates patient prognosis. Aims: Evaluation of cardiac magnetic resonance (CMR) quantified RV global and regional strain of CA and HCM patients along with CA subtypes. Methods: CMR feature tracking attained longitudinal, radial and circumferential global and regional strain in 47 control subjects (CTRL), 43 CA-, 20 hypertrophic cardiomyopathy- (HCM) patients. CA patients were subdivided in 21 transthyretin-related amyloidosis (ATTR) and 20 acquired immunoglobulin light chain (AL) patients. Strain data and baseline clinical parameters were statistically analysed with respect to diagnostic performance and discriminatory power between the different clinical entities. Results: Effective differentiation of CA from HCM patients was achieved utilizing global longitudinal (GLS: 16.5 ± 3.9% vs. −21.3 ± 6.7%, p = 0.032), radial (GRS: 11.7 ± 5.3% vs. 16.5 ± 7.1%, p < 0.001) and circumferential (GCS: -7.6 ± 4.0% vs. −9.4 ± 4.4%, p = 0.015) right ventricular strain. Highest strain-based hypertrophic phenotype differentiation was attained using GRS (AUC = 0.86). Binomial regression found right ventricular ejection fraction (RV-EF) (p = 0.017) to be a significant predictor of CA-HCM differentiation. CA subtypes had comparable cardiac strains. Conclusion: CMR-derived RV global strains and various regional longitudinal strains provide discriminative radiological features for CA-HCM differentiation. However, in terms of feasibility, cine-derived RV-EF quantification may suffice for efficient differential diagnostic support.